Environmentally Friendly Machining - Dixit, U.S.; Sarma, D.K.; Davim, J. Paulo; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
Environment-Friendly Machining provides an in-depth overview of environmentally-friendly machining processes, covering numerous different types of machining in order to identify which practice is the most environmentally sustainable. The book discusses three systems at length: machining with minimal cutting fluid, air-cooled machining and dry machining. Also covered is a way to conserve energy during machining processes, along with useful data and detailed descriptions for developing and utilizing the most efficient modern machining tools. Researchers and engineers looking for sustainable machining solutions will find Environment-Friendly Machining to be a useful volume.
Green Manufacturing -- Machining with Minimal Cutting Fluid -- Dry Machining -- Air-Cooled Machining -- A Comparison of Environment-Friendly Machining Processes -- Offline and Online Optimization of Machining Processes -- Economics of Environmental-Friendly Machining.
Keywords: Engineering; Machinery; Environmental pollution; Engineering; Manufacturing, Machines, Tools; Machinery and Machine Elements; Industrial Pollution Prevention